Colonização e infecção por bacilos gram-negativos (enterobacteriaceae e não fermentadores) em neonatos do berçário de alto risco do Hospital de Clínicas da Universidade Federal de Uberlândia - Cezário, Renata Cristina (2003)
The aim of this study was to determine the incidence of Gram-negative organismis from nosocomial infections, the relationshíp between colonization and infection, the mtnnsic and extrinsec risk factors, the maijor antibiotic resistance phenotys (ESBL and AmpC) incluing an epidemic strain and utilization of third-generation cephalosporins and carbapenems in neonates admitted in the BAR UFU-HC, during 23 mounth period between January, 2001 and December, 2002. A vigilance of the cases of nosocomial infections and use of the p-lactams was achievement through of prospective study and four prevalence of colonization inquerit from September and Novetnber, 2001 and February and August/2002. The synergy test was performed with double-dtsk to detect the samples produciong extended-spectntm P-laetamase. The incidence of infected patients with BGN was 2.4%, including sepse (38.4%) and conjuctivitis (30.5%) wicth were more infections obsetved. The most of infections were endemic and often associated with Enterobacteriaceae family (88.3%), observed a narrow relation between the most frequent Enterobactriaceae and that found when the colonization, corresponding mainiy to samples of Emerobaeter spp. and Klebsiella spp. During of the study were identifled two outbreak, associated the samples by l’seudo„:o,,as aeruginosa (N=10) and Acineiobaeler baumami (N=l I) these last was coincided with the incresed of the consume of carbapenems. At the opposed the endemic infections, the epidemics samples were not detected in assylomatic neoantes. In total 135 neonates included in the prevalence study, were colonizaded with resistant sample to 2 pg/ml of cetazidime mainiy in the intestine (59.0%). The intrinsic risk factors (lengh of hospitalization) and extrinsic (antibiotic use, mecanic ventilation, central venous catheters, siturgical and nutrition parenteral) were more significanty associaded with infections cases. A high frequency was observed among resistant samples of the ESBL phenotypes, as well as the relation with ceflriaxone use in tlje Unit.